Electroconductive Photo-Curable PEGDA-Gelatin/PEDOT:PSS Hydrogels for Prospective Cardiac Tissue Engineering Application - Testore, Daniele; Zoso, Alice; Kortaberria, Galder; Sangermano, Marco; Chiono, Valeria (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract